Determinação in vitro dos compostos bioativos no albedo de maracujá (Passiflora edulis) - ROSÁRIO, Rosely Carvalho do (2023)
The passion fruit industry during pulp and juice processing generates tons of waste, such as albedo. But this byproduct has an important nutritional value and potential to provide a protective effect against degenerative and chronic diseases. Therefore, the aim of this study was to determine in vitro the bioactive compounds in the albedo of passion fruit (Passiflora edulis). The methodologies applied followed internationally accepted and recommended guidelines for the following analyzes of the albedo in natura and FAMDE obtained: preparation and yield of albedos flour, particle size analysis, physicochemical characteristics, contents of bioactive compounds, pectin, technological potential and morphology. The kiln dehydrated albedo resulted in a yield of 9.76%, and from this a semifine powdered flour (75.8%) was prepared, with quality within that recommended by the current national legislation, with its moisture content in 4.95%. The dehydration of this residue provided effective physicochemical characteristics for conservation (Aw= 0.374, pH= 5.293 and ATT=0.99) and good quality (SST= 1.5°Brix and AR=40.72%). In addition, the presence of bioactive compounds was evidenced, mainly in the flour, as traces of polyphenols (18.88 mg AGE/100g), flavonoids (13.51 mg/100g), anthocyanins (1.74 mg/100g) and chlorophyll b (69.65 mg/100g), highlighting a considerable amount of vitamin C (377.36 mg/100g). FAMDE presented fiber bundles in their morphology and relevant pectin concentration (40.5%). Finally, the technological and functional properties of FAMDE were: CAA (862.4%), ISA (12.5%), CAO (252.7%), CEM (22.87%), CFE and EE (not significant), and gelling capacity of 14%, suitable values for applications in the food industry. It was concluded that the use of passion fruit albedo for flour preparation pointed to its results potentially applicable to human health and the food industry, in addition to a reduction in environmental disposal.